QUALITY OF LIFE IN PATIENTS WITH JUVENILE RHEUMATOID ARTHRITIS IN THE CONDITIONS OF TREATMENT WITH CHIMERIC MONOCLONAL ANTIBODIES TO TNF α - R.V. Denisova; E.I. Alexeeva; V.Yu. Al'bitsky; I.V. Vinyarskaya; S.I. Valieva (Вопросы современной педиатрии, 2009)
The article presents results of study of inhibitor TNF α — infliximab — on quality of life in patients with juvenile arthritis, refractory to standard immunosuppressive treatment. In 1.5 months after the beginning of treatment, the quality of life increased in 98% of patients; and in one year, the rates of physical functioning were similar to it in healthy children the same age.Key words: children, juvenile arthritis, quality of life, infliximab.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):18-26)